2019
DOI: 10.4102/aveh.v78i1.493
|View full text |Cite
|
Sign up to set email alerts
|

The ophthalmology postgraduate training programme in South Africa: The registrars’ perspective

Abstract: Background: In South Africa, to become an ophthalmologist, one must successfully complete a 4-year postgraduate training programme as a registrar. This training has been offered at different institutions around the country for many years without ever being scrutinised.Aim: The aim of this study was to evaluate the training methods and platforms, overall satisfaction levels, problems and solutions pertaining to postgraduate ophthalmology training as identified by ophthalmology registrars.Setting: The study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…It may be that these high workloads reflect the clinical demand in the regions supported by STP posts, which typically have fewer ophthalmologists available per capita. 1 However, other international studies of ophthalmology trainees have similarly reported high workloads, 13,14 suggesting this may be a profession specific issue and not reflective of STP posts specifically. Further, it may be that there is overuse of trainee labour to enable greater work/life balance amongst ophthalmologists at STP posts.…”
Section: Discussionmentioning
confidence: 98%
“…It may be that these high workloads reflect the clinical demand in the regions supported by STP posts, which typically have fewer ophthalmologists available per capita. 1 However, other international studies of ophthalmology trainees have similarly reported high workloads, 13,14 suggesting this may be a profession specific issue and not reflective of STP posts specifically. Further, it may be that there is overuse of trainee labour to enable greater work/life balance amongst ophthalmologists at STP posts.…”
Section: Discussionmentioning
confidence: 98%
“…[3][4][5][6] New researchers may encounter many obstacles during their groundwork; scrutinising these factors to reduce their impact may therefore increase research accuracy, success and output. [1,[8][9][10][11][12][18][19][20] A lack of protected academic time away from service work is an issue much cited by registrars nationally and internationally. This situation can be compounded by poor patient record-keeping, which may extend the data collection period.…”
Section: Discussionmentioning
confidence: 99%
“…[3,[6][7][8][9][10] Issues raised in previous publications include lack of time (including academic time), lack of supervision and support, poor communication, and a need for training in research methodology. [3,8,[10][11][12] There is also a need to investigate strategies to improve the current research infrastructure for those enrolled in specialisation training, enabling them to conduct impactful and relevant research. Improved infrastructure includes ease of access to patient records.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17 No reliable and consistent statistics are available on the overall number of ophthalmologists practising in South Africa or the locations of their practices. 25 From a recent study on funding health care benefits by medical schemes, approximately 511 ophthalmologists claim from medical schemes. 26 The latter provide further credence to the statistic indicating that the private sector employs 85% of active ophthalmologists (again, distribution is skewed to the private sector).…”
Section: Ophthalmologistsmentioning
confidence: 99%